Westernizing the Third World : the eurocentricity of economic development theories - Mehmet, Ozay (Routledge, 2002)
The second edition of this successful and popular text has been updated and revised to include recent issues in development economics. Significant new additions include:* Asian values and development* democracy, human rights and good governance* globalization and development* boxed summaries of key arguments and glossary. Westernizing the Third World identifies the mainstream economic theories which have been employed in developing countries. The author examines these and explains why Eurocentric concepts are not suitable for the developing world.